Plasmonic Biosensor Based on Vertical Arrays of Gold Nanoantennas - Klinghammer, Stephanie; Uhlig, Tino; Patrovsky, Fabian; Boehm, Matthias; Schuett, Julian; Puetz, Nils; Baraban, Larysa; Eng, Lukas M.; Cuniberti, Gianaurelio (Giovanni) (ACS Sensors, 2018)
Implementing large arrays of gold nanowires as functional elements of a plasmonic biosensor is an important task for future medical diagnostic applications. Here we present a microfluidic-channel-integrated sensor for the label-free detection of biomolecules, relying on localized surface plasmon resonances. Large arrays (∼1 cm2) of vertically aligned and densely packed gold nanorods to receive, locally confine, and amplify the external optical signal are used to allow for reliable biosensing. We accomplish this by monitoring the change of the optical nanostructure resonance in the presence of biomolecules within the tight focus area above the nanoantennas, combined with a surface treatment of the nanowires for a specific binding of the target molecules. As a first application, we detect the binding kinetics of two distinct DNA strands as well as the following hybridization of two complementary strands (cDNA) with different lengths (25 and 100 bp). Upon immobilization, a redshift of 1 nm was detected; further backfilling and hybridization led to a peak shift of additional 2 and 5 nm for 25 and 100 bp, respectively. We believe that this work gives deeper insight into the functional understanding and technical implementation of a large array of gold nanowires for future medical applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: DNA biosensor; gold nanowires; localized surface plasmon resonances (LSPR); nanoantenna; plasmonic biosensors; refractometry; template assisted assembly of nanorods